Development of Novel 4‐Arylpyridin‐2‐one and 6‐Arylpyrimidin‐4‐one Positive Allosteric Modulators of the M1 Muscarinic Acetylcholine Receptor. (25th September 2020) - Jörg, Manuela; Khajehali, Elham; van der Westhuizen, Emma T.; C. Choy, K. H.; Shackleford, David M.; Tobin, Andrew B.; Sexton, Patrick M.; Valant, Celine; Capuano, Ben; Christopoulos, Arthur; Scammells, Peter J.
Abstract: This study investigated the structure‐activity relationships of 4‐phenylpyridin‐2‐one and 6‐phenylpyrimidin‐4‐one M1 muscarinic acetylcholine receptor (M1 mAChRs) positive allosteric modulators (PAMs). The presented series focuses on modifications to the core and top motif of the reported leads, MIPS1650 (1 ) and MIPS1780 (2 ). Profiling of our novel analogues showed that these modifications result in more nuanced effects on the allosteric properties compared to our previous compounds with alterations to the biaryl pendant. Further pharmacological characterisation of the selected compounds in radioligand binding, IP1 accumulation and β‐arrestin 2 recruitment assays demonstrated that, despite primarily acting as affinity modulators, the PAMs displayed different pharmacological properties across the two cellular assays. The novel PAM 7 f is a potential lead candidate for further development of peripherally restricted M1 PAMs, due to its lower blood–brain‐barrier (BBB) permeability and improved exposure in the periphery compared to lead 2 . Abstract : The same, but different : An in‐depth pharmacological evaluation with functional IP1 accumulation and β‐arrestin 2 recruitment assays as well as radioligand binding assays has determined the structure–activity relationships of novel M1 acetylcholine receptor positive allosteric modulators. Despite acting primarily as affinity modulators, they have diverse pharmacological profiles, thus providing leads for the further development of peripherally restricted ligands.